Characteristics of a CaSO4 oxygen carrier for chemical-looping combustion: reaction with polyvinylchloride pyrolysis gases in a two-stage reactor. Issue 44 (16th May 2015) - Bi, Wenzhuo; Chen, Tianju; Zhao, Ruidong; Wang, Zhiqi; Wu, Jingli; Wu, Jinhu
<x xml:space="preserve">Abstract</x> Chemical-looping combustion (CLC), which is a promising technique that includes an inherent separation of CO2 may reduce the generation of dioxins in municipal solid waste (MSW) disposal because in a CLC system, no free oxygen is available for incineration process.